Proyecto de factibilidad para la creación de una empresa productora y comercializadora de gel natural a base de linaza en la ciudad de Loja - Apolo Ríos, Edgar Alexander (2022)
The product to consider in this feasibility study is a hair gel based on flaxseed, the vitamins provided by this product make the scalp softer and healthier, it prevents dandruff, making it a natural molding. This is why it is considered to evaluate the feasibility of building a plant in the city of Loja, where the gel is produced and sold. To do this, the following studies were carried out: market, technical, administrative, legal and financial, each of them to obtain better decision-making about the implementation and management of the project. Market research shows that the final segment of the market is 149.807 people, living in the city of Loja, from 15 to 40 years of age. Likewise, the sale price of the product is fixed, for $4.60. The technical study determines the size and location of the project, providing specific weights based on macroeconomic factors, where it shows at the macro level that the location of the project will be in the city of Loja, at the micro level, the company will be installed in Esteban Godoy, Héctor Pilco street and Germán Pitiur. Likewise, in the last projected year it will have an installed capacity of 22%. Administrative-legally, it is estimated that it consists of a staff of 10 people who provide a job description. In the financial study, the total amount of assets to be invested is $34.080,20 of which 40% will be financed by BanEcuador with an interest rate of 10.21% on the amount of the 3-year term investment. As a final step, the economic evaluation is carried out using the npv, giving a result of 35.477,15 then the irr with a result of 44%. Finally, a sensitivity analysis where it is identified whether the creation of the company will be feasible, where it shows that the company can withstand an increase in costs of 12% and sensitivity analysis where it shows that it can withstand a decrease in revenue of 9%.